Juridizaciones en las fronteras: Procesos de misionalización y construcción de derecho indígena en Paraguay y Argentina (1978-1984) - Leone, Miguel (2023)
The text analyzes processes of indigenous missionization generated in the1970s/80s in the Chaco territories of Paraguay and Argentina. It explores the existing relationships between Christian pastoral agents settled on both sides of the national border, and suggests that such links were a relevant element to understand the dynamics of the sanction and content of the Integral Aboriginal Law in the province of Formosa (1984) -located in the extreme northeast of Argentina. The analysis is based on the concepts of juridization, aboriginal pastoral and frontier. The first one is necessary to think about the historical process through which legislations are produced. Aboriginal pastoral, on the other hand, is a native term that refers to various Christian ecclesiastical actors (bishops, priests, consecrated lay men and women, nuns, seminarians, Protestant pastors, among others) who since the sixties of the 20th century dedicated themselves to working and living alongside native peoples, imprinting their practice with a certain "liberationist" sense. The term native is conceptualized here to understand this collective subject and the space of indigenist Christian sociability in which it was configured. Finally, the concept of frontier is necessary to analyze the different border dynamics that took place in the historical process under study (concept/object, concept/metaphor, border, frontier and ethnic frontiers). Methodologically, the article draws on historical documents, periodical publications and the analysis of secondary sources.